Evaluation of HMA cracking resistance as a function of laboratory aging based on the direct-tension test (2011)
Hot mix asphalt (HMA) is a heterogeneous composite material of asphalt-binder, aggregates, air voids, and other additives including lime, fibers, etc., predominantly used for pavement construction. With time, the HMA mix ages, which leads to changes in the material properties and response behavior. This paper documents a laboratory study that was conducted to evaluate the suitability of the direct-tension (DT) test to assess the effects of asphalt-binder aging on the HMA mix fracture properties and cracking-resistance potential. Two dense-graded HMA mixes were subjected to different laboratory aging exposure conditions and then tested with the DT test. From this test, the HMA mix fracture response was characterized in terms of the tensile strength, tensile strain at peak failure load, stiffness, and fracture energy. Overall, the results indicated that asphalt-binder aging has a detrimental effect on the fracture response and cracking-resistance of HMA mixes, which can be captured based on the DT test. Therefore, the asphalt-binder aging needs to be considered and properly accounted for during the material design and analysis stages of HMA mixes. However, research with more HMA mixes and correlation with field data is strongly recommended to validate the laboratory findings reported in this paper.